b primer /c - Hoy, Wayne K.; Adams, Curt M. (b, 2016)
Quantitative Research in Education is a brief and practical guide to conducting research in Education. It provides a reference point for beginning educational researchers to grasp the most pertinent elements of designing and conducting research.
Includes bibliographical references and index.
Keywords: v; Quantitative research; Education